Pengaruh Senam Ergonomik Terhadap Penurunan Tekanan Darah Di Desa Setia Suka Kabupaten Tapanuli Utara 2023 - Christo Christo; Citra Dewi Fitri; Nurhayani Harahap (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
This study aims to evaluate the impact of ergonomic exercises on blood pressure in hypertensive patients in the village of Setia Suka Maju Sirihit – Rihit. The research employed a One Group Pre-test – Post method using purposive sampling, with 10 respondents selected from a population of 50 who met the criteria. Data were collected using an ordinal scale and observational instruments. The results of the Wilcoxon Signed Ranks Test using SPSS indicated significance < 0.05 (p=0.00), signifying the influence of ergonomic exercises on lowering blood pressure. The conclusion of this study asserts the effectiveness of ergonomic exercises in reducing blood pressure in hypertensive patients in Setia Suka Maju Sirihit – Rihit Village, Pahae Jae Subdistrict, North Tapanuli Regency in 2023.